From protest to parties party-building and democratization in Africa - LeBas, Adrienne (Oxford : Oxford University Press, 2011)
'From Protest to Parties' provides a unique window into the politics of mobilization and protest in closed political regimes, shedding light on how the choices of political elites affects organizational development.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Political parties -- Zimbabwe; Political parties -- Zambia; Political parties -- Kenya; Opposition (Political science) -- Zimbabwe; Opposition (Political science) -- Zambia; Opposition (Political science) -- Kenya; Zimbabwe -- Politics and government -- 1980-; Zambia -- Politics and government -- 1991-; Kenya -- Politics and government -- 2002-